Policy Implementation of The Duties and Functions of Family Planning Field Officers (P.L.K.B.) Non-Civil Servant at The Department of Population Control and Family Planning - Mamahit, Serly Lian; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
In general, this study aims to describe and analyze the Implementation of the Policy on Duties and Functions of Non-civil servant Family Planning Field Officers (P.L.K.B.) at the Department of Population Control and Family Planning, Southeast Minahasa Regency. This study uses a qualitative research type, primary data collected through interview techniques, and supported by secondary data, namely documentation. The data analysis of this research used an interactive model consisting of "data collection, data display, data condensation, concluding; drawing and verifying" developed by Miles, Huberman, and Saldana. The results of this study prove that; The implementation of the P.L.K.B. Duties and Functions Policy is based on the Decree of the Southeast Minahasa Regent Number: 180/13/S.E.T.D.A./2021 concerning the Appointment of Contract Workers, Cleaning Officers, Drivers, and other Officers within the Southeast Minahasa Regency Government. Whereas the main tasks of non-civil servant P.L.K.B. are not much different from that of civil servant P.L.K.B., namely, approach Community Leaders; carry out data collection and mapping of work areas; conduct agreement-raising, conduct I.E.C. counselling/counselling, and advocacy; establish a pioneer and role model group, family planning services, adolescent reproductive health, prosperous families, and family development; make a report on the implementation of tasks to the leadership. Therefore, the Family Planning Field Officer (P.L.K.B. non-civil servant) controls and owns it to carry out the lessons. In carrying out these duties, non-civil servant Family Planning Field Officers can improve their abilities and skills. The main problems faced are related to the duties and functions of non-civil sservantsP.L.K.B. The number of villages is so large that it is not proportional to non-civil servant P.L.K.B. personnel. The facilities and infrastructure owned to support the tasks of P.L.K.B. Non-civil servants are still inadequate. Non-civil servant, P.L.K.B. cooperation with cross-sector (District and Village), is less than optimal. The human resource capabilities of P.L.K.B. non-civil servants are also not yet professional. Non-civil servant P.L.K.B. compensation has not provided adequate guarantees when compared to the duties. So that a wiser policy is needed, namely, "Regulation or Regent's Decree Regarding: Guidelines for the Management, Duties, and Functions of Family Planning Field Officers (P.L.K.B.) for Non-civil servant Southeast Minahasa Regency, which in this policy includes rights and obligations, sanctions and rewards and others deemed necessary. Non-civil servant P.L.K.B. is an officer who implements, manages, and mobilizes the community in the Proud of program planning at the village level. Non-civil servant P.L.K.B. is very helpful in the lack of Family Planning Extension Workers (P.K.B.) in the field.